Cardiac conduction system as a new organ at risk in radiotherapy - Domanský, M; Kubeš, J (Klinicka onkologie, 2024)
BACKGROUND: Cardiovascular diseases represent the most common non-oncologic cause of death in patients following radiotherapy (RT) in the thoracic region. Radiation-induced heart disease (RIHD) can manifest as various heterogeneous clinical entities. However, the influence of RT on the cardiac conduction system has only recently gained more attention. Arrhythmogenic toxicity, i.e., conduction disorders and arrhythmias, constitutes a significant part of these adverse effects. The cardiac conduction system is not routinely monitored as an organ at risk (OaR). Its specific histological nature and function suggest different sensitivity and response to radiation. The heart is a highly heterogeneous organ, and the routinely monitored dose to the whole heart may not adequately characterize the risk of increased arrhythmogenic toxicity from RT. Cardiac structures, including the conduction system, appear to be additional OaRs for which dose distribution should be monitored. MATERIAL AND METHODS: For the systematic selection of studies, we utilized the PubMed database with keywords derived from the analysis of existing literature. The search was limited to English-language publications, and the selection criteria included relevance to the topic and the quality of methodology. PURPOSE: This article summarizes the impact of RT on the cardiac conduction system. CONCLUSION: Radiotherapy-induced cardiotoxicity significantly affects morbidity and mortality. The heart exhibits heterogeneity in terms of radiosensitivity. Certain cardiac subregions in the dose distribution show a higher correlation with poorer overall survival than routinely monitored doses to the whole heart and derived parameters (the volumes irradiated with the doses of 5 or 30 Gy - V5 or V30, respectively). The most radiosensitive subregions appear to be the base of the heart, including the beginning of the conduction system. Higher doses to the conduction system, especially the sinoatrial (SA) node, are associated with a higher incidence of a wide range of arrhythmias and poorer overall survival. However, dose limits (Dmean and Dmax) for the conduction system have not yet been established. Dosimetric studies have identified cutoff doses to the SA node, exceeding which there is a significant increase in mortality and the occurrence of arrhythmias.
Keywords: arrhythmias, cardiac; organs at risk; převodní systém srdeční; radioterapie; Organs at Risk; Radiation Injuries; kritické orgány; radiation injuries; Humans; srdeční arytmie; Radiotherapy; Arrhythmias, Cardiac; Heart Conduction System; cardiotoxicity; heart conduction system; sinoatrial node; lidé; radiační poranění